PENGARUH BUDAYA, LINGKUNGAN DAN MOTIVASI TERHADAP PRESTASI KERJA PEGAWAI BADAN PENDIDIKAN DAN PELATIHAN SUMATERA SELATAN - Sutripto, Sutripto (Jurnal Ilmu Manajemen, 2013)
The purpose of this research is to know the influence of culture, environment, and motivation for employee performance of Training Center of South Sumatera employees not only jointly but also partially which usedpurpose sampling which is the third group employees of Training Center is 76 employees. Descriptive data analysis done after the data is converted to a form of interval using the Successive Interval. Multiple linier regression analysis done which is helped by SPSS Program for Windows version 16 to test the research hypothesis T test analysis results proved that culture, environment, and motivation variables have real influence for employee performance of Training Center ofSouth Sumatera employees which the constants is 2,085. Culture variable have real influence which is have regression constants 0,779 and motivation of employee have real influence which is have regression constants 0,4124.F test analysis results proved that F-arithmetic is 80,863 bigger than F-table of ? 0,05 = 2,737. It means that if the error rate 0,05, it will influence culture, environment, and motivation of employee jointly for employee performanceof Training Center of South Sumatera